2017
DOI: 10.1007/s15010-017-1099-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of comprehensive multidisciplinary antibiotic stewardship programs centered on weekly prospective audit and feedback

Abstract: The comprehensive ASPs had long-term efficacy for reducing the use of the targeted broad-spectrum antibiotics, maintaining the antibiotic susceptibility of P. aeruginosa, and decreasing the prevalence of MRSA, without adversely affecting clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Honda et al reported that the initiation of adequate empiric antimicrobial therapy had important implications for AS even in the elderly population in Japan [9]. Other studies have also discussed AST and infectious disease control from the point of view of physicians, pharmacists, or clinical microbiologists [6,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Honda et al reported that the initiation of adequate empiric antimicrobial therapy had important implications for AS even in the elderly population in Japan [9]. Other studies have also discussed AST and infectious disease control from the point of view of physicians, pharmacists, or clinical microbiologists [6,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Our study was conducted with a well-established AST over five years [6]. Statistical analyses showed that the percentage of cases of inappropriate broad-spectrum antibiotic use and interventions for indefinite infections had significantly decreased, whereas the number of blood or drainage culture submissions had significantly increased over the five-year study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Kimura [17], which evaluated the long-term effects of antibiotic administration programs at a university hospital in Japan, found that therapy days per 1000 patient-days were higher for 1st generation cephalosporins (45 DOT / 1000pd). The time of use of quinolones (4.7 DOT / 1000pd) and carbapenems (13.5 DOT / 1000pd) were well below the values veri ed in this study.…”
Section: Discussionmentioning
confidence: 99%